Sleep Disturbance and Immunological Consequences of COVID-19 - Bocek, Jonas; Prasko, Jan; Genzor, Samuel; Hodny, Frantisek; Vanek, Jakub; Pobeha, Pavol; Belohradova, Kamila; Ociskova, Marie (Patient preference and adherence, 2023)
The overarching importance of sleep was further emphasized during the pandemic of COVID-19. The subjects infected by COVID-19 frequently experience sleep disturbances; some are long-lasting problems and decrease the quality of life. Insomnia is the most studied sleep disorder associated with COVID-19. Insomnia affects patients who have experienced an infection and the general population. Good sleep is important in maintaining mental and physical health, including immune system functions. The interconnections between insomnia, the immune system, and COVID-19 are complex. Insomnia triggers numerous immune system dysregulations and makes individuals more vulnerable to respiratory infections. This narrative review overviews the influence of the COVID-19 pandemic on the immune system through sleep disorders.
Keywords: insomnia; immunity; sleep deprivation; circadian rhythms; COVID-19; mental disorders